ANALISIS SEMANTIK PADA PENAMAAN DIRI MAHASISWA DI PROGRAM STUDI PENDIDIKAN JASMANI UNIVERSITAS MUHAMMADIYAH KOTABUMI - Windo Dicky Irawan (Universitas Muhammadiyah Kotabumi, 2020)
Abstract: Semantic Analysis Research on the Self-Naming of the fourth semester of Physical Education Study Program at the University of Muhammadiyah Kotabumi University sourced from the names of students in the academic year 2018/2019 in class A (morning). Muhammadiyah University Kotabumi is a Muhammadiyah College (PTM) in North Lampung district which has interesting meanings in the students' self names. Based on the findings of the analysis, there are elements of naming from Javanese language and culture, naming that uses elements of foreign languages ​​(English, Arabic, Scottish), and from the combined elements of the names of parents or descendants in these names. This is the basis for researchers to study, especially those related to the language of elements and meanings contained in the name of the fourth semester Physical Education Study Program students at Muhammadiyah University, Kotbaumi. Understanding of the language of the elements and types of meaning can be known based on language as forming elements of student names and the types of meanings contained therein.